Impact of Assistive Technology on Reading Comprehension Skills in Students with Learning Disabilities - Aftab, Muhammad Javed; Irfan, Narmeen; Amjad, Faisal (Annals of Human and Social Sciences, 2024)
This study examines the difficulties encountered during the adoption of assistive technology (AT) and proposes successful approaches. It also investigates the influence of AT on reading comprehension abilities of children with learning disabilities. Integration of AT in classroom has revolutionized the delivery of education for students with learning challenges. AT encompasses a diverse array of digital technologies designed to enhance academic performance and functional capabilities. Graphic organizers and text-to-speech softwares are tools that support the creation of personalized learning environments in accordance with the principles of Universal Design for Learning (UDL). Two hundred special education teachers took part in a quantitative methodology. Findings indicate that educators had predominantly favorable perceptions, with significant in claimed advantages depending on gender, designation and region. In order to optimize the integration of AT in inclusive educational practices, it is recommended to prioritize research activities, push for governmental funding, enhance professional development and foster cooperative collaborations.